PERTEMANAN SEBAYA SEBAGAI ARENA PENDIDIKAN DERADIKALISASI AGAMA - Yusar, Yusar (WALISONGO, 2015)
This article was an endeavor to describe the arena of the education which aim tode-radicalization, specially among the youth with their peer group. In many cases,the youth is the main target of the radicalism and they were often exploited for theradical movement. In previous researches, the concept of the peer group arerarely considered. Data collected based on several observations in the experimentswith the artificial scene of daily life. The youth found their way to showtheir awareness on the religious radical movement. In some empirical investigations,this article might offers the theoretical framework of peers that may beconstructed to study the de-radicalization of religious movement. In the peer life,it was built the force to control the members not to join the radical movement.This article may provide a new approach in terms of education for deradicalizationof religious movement.***Artikel ini merupakan upaya untuk menggambarkan arena pendidikan yang bertujuanuntuk deradikalisasi, khususnya di antara kaum muda dengan kelompoksebaya mereka. Dalam banyak kasus, pemuda adalah sasaran utama radikalismedan mereka sering dilakukan untuk gerakan radikal. Dalam penelitian sebelumnya,konsep dari kelompok sebaya jarang dipertimbangkan. Data dikumpulkanberdasarkan beberapa pengamatan dalam eksperimen dalam adegan buatankehidupan sehari-hari. Pemuda menemukan jalan mereka untuk memberikantanda kesadaran gerakan radikal agama. Pada beberapa penyelidikan empiris,artikel ini dapat menawarkan kerangka teoritis teman sebaya yang mungkindibangun untuk mempelajari deradikalisasi gerakan keagamaan. Dalam kehidupanteman sebaya, dibangun kekuatan untuk mengendalikan anggota untuk tidakbergabung dengan gerakan radikal. Artikel ini dapat memberikan pendekatanbaru dalam pendidikan istilah untuk deradikalisasi gerakan keagamaan.